Optimization of E. coli Cultivation Model Parameters Using Firefly Algorithm - Olympia Roeva; Olympia Roeva (International Journal Bioautomation, 2012)
In this paper, a novel meta-heuristics algorithm, namely the Firefly Algorithm (FA), is adapted and applied for a model parameter identification of an E. coli fed-batch cultivation process. A system of ordinary nonlinear differential equations is used to model the biomass growth and substrate utilization. Parameter optimization is performed using real experimental data set from an E. coli MC4110 fed-batch cultivation process. The FA adjustments are done based on several pre-tests according to the optimization problem considered here. The simulation results indicate that the applied algorithm is effective and efficient. As a result, a model with high degree of accuracy is obtained applying the FA.